2020
DOI: 10.15376/biores.15.4.saxena
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacies of microbes for mitigation of Azo dyes in textile industry effluent: A review

Abstract: In recent years, India has emerged as a promising industrial hub. It has a cluster of textile, dyeing, and printing industries. The adjoining rivers/water bodies receive mostly untreated discharge from these industries. Textile industrial effluent contains various contaminants (dyes, heavy metals, toxicants, and other organic/inorganic dissolved solids) that alter the physico-chemical properties of adjoining land and waterbodies in which it is discharged, thereby degrading the water quality and subsequently af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…For the widespread application of bacterial bioremediation, several factors have to be considered, depending on the technique used, the characteristics of the environment to be remediated and of the bacteria strain, in this sense, the following points are relevant bottlenecks for large-scale application: (1) Bioreactor implementation and maintenance costs, (2) physicochemical parameters-which may vary over time, (3) space available for use of, e.g., wetlands or bioreactors, (4) availability of nutrients in the environment or in the textile effluent to be decontaminated, (5) presence/generation of suitable redox mediators for the enzymatic action of azo bond breaking, (6) engineering optimization in the transition from laboratory/pilot to industrial scale, (7) stricter local legislation forcing companies to treat their effluents properly, (8) co-relation between dye and bacteria/bacterial consortia or the presence of mixed dyes that can affect the bleaching given the bacterial suitability to each dye, (9) the use of industrial chemicals not considered in the laboratory tests, (10) changes in industrial dyeing techniques that modify the characteristics of its effluent and require adaptation of the bioremediation technique used, and (11) generation of toxic by-products that bacteria are not able to degrade, among other factors more specific to the numerous systems under study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the widespread application of bacterial bioremediation, several factors have to be considered, depending on the technique used, the characteristics of the environment to be remediated and of the bacteria strain, in this sense, the following points are relevant bottlenecks for large-scale application: (1) Bioreactor implementation and maintenance costs, (2) physicochemical parameters-which may vary over time, (3) space available for use of, e.g., wetlands or bioreactors, (4) availability of nutrients in the environment or in the textile effluent to be decontaminated, (5) presence/generation of suitable redox mediators for the enzymatic action of azo bond breaking, (6) engineering optimization in the transition from laboratory/pilot to industrial scale, (7) stricter local legislation forcing companies to treat their effluents properly, (8) co-relation between dye and bacteria/bacterial consortia or the presence of mixed dyes that can affect the bleaching given the bacterial suitability to each dye, (9) the use of industrial chemicals not considered in the laboratory tests, (10) changes in industrial dyeing techniques that modify the characteristics of its effluent and require adaptation of the bioremediation technique used, and (11) generation of toxic by-products that bacteria are not able to degrade, among other factors more specific to the numerous systems under study.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario generates serious consequences for the contaminated environment, such as interference with the entry of sunlight into the water, influencing photosynthetic organisms, causing damage to the oxygen level of the water, metabolic stress, neurosensorial damage, flora necrosis, death, and decreased growth of fauna, among others. Moreover, humans are also potential victims of these compounds, when discharged into nature without treatment, and can be quite toxic, either by oral or respiratory ingestion as well as mere skin contact [2,5,6]. The toxic effects of azo dyes, in particular their ability to promote mutations, are related both to the dyes themselves and to metabolites released upon their breakage or degradation, such as aromatic amines.…”
Section: Of 23mentioning
confidence: 99%
“…While dyes and pigments are used in diverse commercial applications, innovative and sustainable effluent treatment processes must be implemented to reduce their environmental impact. Despite the fact that dyes are stable and difficult to degrade, the capacity of fungi to degrade such pollutants has been widely studied and their potential for use in the bioremediation of dye wastewater represents an opportunity not only for resource recovery, but also for environmental sustainability [2,11,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing preference, in general terms, for the application of modern biological techniques to tackle different environmental problems. As biological remediation is considered more efficient in terms of its long-lasting benefits and minimal harmful effects on the environment, conducting biodegradation via the use of different microorganisms appears to be an alternative [11,12]. Although many bacteria are able to degrade synthetic dyes under anaerobic conditions, in these circumstances the dyes are usually reduced to even more toxic aromatic amines.…”
Section: Introductionmentioning
confidence: 99%
“…Both observed outcomes showed effective decolorization with minimum nutrient loss. As a result, it was found that anaerobic conditions result in high dye degradation and declourization of textile effluents [40]. 2) Aerobic Decolorization Process: Waste activated sludge treatment has proven to be cost-efficient in lowering organic contaminants from wastewater systems.…”
Section: Bacterial Decolourizationmentioning
confidence: 99%